Adaptation Strategies to Climate Change Impacts in The Area of Sidenreng Lake, Sidenreng Rappang Regency - Nurhidayanti Alfath; Mukti Ali; Mimi Arifin (PENA TEKNIK: Jurnal Ilmiah Ilmu-Ilmu Teknik, 2023)
The research site is one of the high-risk flood district zones along with Panca Lautang, Tellu Limpoe, and Wattang Sidenreng District since it is adjacent to Sidenreng Lake. The issue allied to climate change at the research site is a real phenomenon in which high rainfall occurs, leading the lake water to overflow and the weather, which previously could be calculated by the community in various ways, is currently unpredictable. The clime vulnerability analysis was utilized at the outset of this study to figure out the level of climate vulnerability. Secondly, Spatial Analysis using ArcGIS Software with Overlay Method towards each flood parameter to address the level of high-risk flood at the site of the research. The third analysis used in this research was AHP-SWOT to formulate some alternative strategies to overcome flood disasters brought about by climate change in the area of Lake Sidenreng. The results of the study showed that the level of flood vulnerability was Very Vulnerable, with 130.94 km2, Vulnerable at 134.98 km2, Quite Vulnerable at 88.93 km2, Less Vulnerable at 22.97 km2, and Not Vulnerable at 3.03 km2 with the total amount of 380.85 km2. Subsequently, the analysis results of the climate vulnerability from 27 villages, 14 of which are at a very low level (Class I), 2 villages are at a low level (Class II), 4 villages are at a Medium level (Class III), and 1 village which is Wette Village is at a very high level (Class IV). According to alternative strategy on AHP-SWOT Analysis, it was found that the space matrix is at Quadrant III of the W-O Strategy namely 1) the development of human resources and public role to nourish environmental hygiene and increase the capacity of vulnerable groups by empowering society with several trainings to improve human resources and group capacity and promoting awareness among people who lived in those vulnerable areas to maintain environmental conditions, the formation of climate villages and the formation and development of disaster care communities to minimize the impact of flood disasters that occurred as a result of climate change; 2)Â  Management of climate change risk by local government and stakeholders either structurally or physically (engineering the built environment, technological choices and environment-based services or institutional-based services (choices in law and regulation, economics, policies and programs of government) by involving potential experts; 3) development of flood susceptibility maps and climate change vulnerability risks that are integrated with disaster mitigation maps so that people figure out the areas which have a large impact on climate change disasters